PENGARUH KUALITAS KEHIDUPAN KERJA DAN KOMPETENSI TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI KEPUASAN KERJA (Studi pada Perawat Badan Layanan Umum Daerah Rumah Sakit Umum Kajen Kabupaten Pekalongan) - Nur Kholik, 1442020122 (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study was conducted to analyze the effect of the quality of work life, the competence of the organizational commitment and job satisfaction as mediation Kajen nurse at General Hospital, as well as to prove the five hypothesis that the lift in this study. Researchers used several theories to explain the four variables consisting of definitions, dimensions and indicators as outlined in the questionnaire as a tool to search for primary data from respondents with Likert scale. Data obtained from the questionnaire in though and analyzed with SPSS and results: the quality of working life has positive effect on job satisfaction, competence significant effect on job satisfaction, satisfaction keja significant effect on organizational commitment, competence no significant effect on organizational commitment, job satisfaction mediates the influence QWL the organizational commitment, but its direct effect greater job satisfaction mediates the full effect of competence to organizational commitment. An increase or decrease in the competence of nurses BLUDs RSU Kajen no direct impact on their organizational commitment, the higher the job satisfaction of nurses will increase the organizational commitment of nurses. Keywords: QWL, competence, job satisfaction, organizational commitment.